2013
DOI: 10.1061/(asce)su.1943-5428.0000091
|View full text |Cite
|
Sign up to set email alerts
|

GPS and GLONASS Static and Kinematic PPP Results

Abstract: Precise point positioning (PPP) involves observations from a single global navigation satellite system (GNSS) receiver and benefits 4 of satellite orbit and clock products obtained from the global infrastructure of permanent stations. PPP avoids the expense and logistic diffi-5 culties of deploying a network of GNSS receivers around survey areas in isolated places, such as the arctic or less populated areas. Potential 6 accuracies are at the centimeter level for static applications and at the subdecimeter leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 13 publications
0
18
0
3
Order By: Relevance
“…In the case of poor availability of GPS satellite due to signal obstruction or weak geometry, a possible solution, among others (use supplementary sensors e.g. accelerometers [2,3], Robotic Total Station [4,5], Locata [6,7], UWB [8]), is the combination of GPS and other GNSS constellation [9][10][11]. The combination of two or more satellite systems offers more visible satellites to users, and that will enhance the satellite geometry with the expectation of improving the overall positioning solution [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of poor availability of GPS satellite due to signal obstruction or weak geometry, a possible solution, among others (use supplementary sensors e.g. accelerometers [2,3], Robotic Total Station [4,5], Locata [6,7], UWB [8]), is the combination of GPS and other GNSS constellation [9][10][11]. The combination of two or more satellite systems offers more visible satellites to users, and that will enhance the satellite geometry with the expectation of improving the overall positioning solution [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…From 1990's to the present, many researchers have focused on the theory and application of the PPP technique (Zumberge et al 1997;Kouba and Héroux, 2001;Gao and Shen, 2002;Kouba, 2003;Choy et al 2007;Geng et al 2010;Martín et al 2011;van Bree and Tiberius, 2012;Alkan and Öcalan, 2013;Anquela et al 2013). …”
Section: Introductionmentioning
confidence: 98%
“…Although the PPP technique was initially applied to GPS observations, the availability of the precise products provided an opportunity to use the PPP for the combination of GPS and GLONASS observations. In the last decade, the PPP with combination of GPS and GLONASS has attracted the attention of many researchers for both static and kinematic applications (Cai and Gao, 2007;Azab et al 2011;Alcay et al 2012;Angrisano et al 2013;Anquela et al 2013;Cai and Gao, 2013;Chen et al 2013;Choy et al 2013;Tu et al 2013;Afifi and El-Rabbany, 2014;Dawidowicz and Krzan, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…In the GNSS based troposphere modeling, the zenith wet delay w Z Moreover, the number of globally distributed stations with GLONASS tracking capability is increasing (See Figure 2 in Fritsche et al (2014)). Thus, increasing studies started to explore the performance of GLONASS-only precise positioning (Cai and Gao, 2013;Anquela et al, 2013;Lou et al, 2015). The results of Cai and Gao (2013) based on 15 high-latitude International GNSS Service (IGS) stations indicated that the GLONASS-only PPP can reach an comparable accuracy to GPS-only PPP.…”
Section: Gps+glonass Ionosphere-free Observation Modelmentioning
confidence: 99%